2012
DOI: 10.1161/hypertensionaha.112.195065
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Angiogenic Factors and Risk of Adverse Maternal and Perinatal Outcomes in Twin Pregnancies With Suspected Preeclampsia

Abstract: To evaluate whether angiogenic factor levels correlate with preeclampsia-related adverse maternal and perinatal outcomes in women with twin pregnancy, we studied 79 women with suspected preeclampsia in the 3rd trimester. Anti-angiogenic soluble fms-like tyrosine kinase 1 (sFlt1) and pro-angiogenic placental growth factor (PlGF) were measured at presentation on an automated platform. An adverse outcome was defined as hemolysis elevated liver enzymes and low platelets syndrome; disseminated intravascular coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 28 publications
12
71
1
1
Order By: Relevance
“…Further, we identified that both urinary PRL levels and the presence of antiangiogenic PRL fragments in urine are superior to circulating concentrations of sFlt-1/PlGF ratio and sEng in predicting the risk of combined adverse maternal outcomes, as well as of all specific adverse outcomes studied. We thus have confirmed and extended previous observations 21,22 as to the association between the circulating sFlt-1/PlGF ratio at the time of initial evaluation and subsequent adverse outcomes in women with singleton or twin pregnancies with suspected preeclampsia; additionally, those studies found an inverse correlation between the sFlt-1/PlGF ratio and the time elapsed between presentation and delivery as we did in the present study. However, we found a greater negative correlation between urinary PRL levels and time elapsed between sampling and delivery when compared with the sFlt-1/PlGF ratio or serum concentrations of sEng.…”
Section: Discussionsupporting
confidence: 92%
“…Further, we identified that both urinary PRL levels and the presence of antiangiogenic PRL fragments in urine are superior to circulating concentrations of sFlt-1/PlGF ratio and sEng in predicting the risk of combined adverse maternal outcomes, as well as of all specific adverse outcomes studied. We thus have confirmed and extended previous observations 21,22 as to the association between the circulating sFlt-1/PlGF ratio at the time of initial evaluation and subsequent adverse outcomes in women with singleton or twin pregnancies with suspected preeclampsia; additionally, those studies found an inverse correlation between the sFlt-1/PlGF ratio and the time elapsed between presentation and delivery as we did in the present study. However, we found a greater negative correlation between urinary PRL levels and time elapsed between sampling and delivery when compared with the sFlt-1/PlGF ratio or serum concentrations of sEng.…”
Section: Discussionsupporting
confidence: 92%
“…The predictive accuracy for preeclampsia-associated complications was best for the sFlt-1/PlGF with an area under the receiver operating characteristics curve of 0.89 and significantly better than other clinical tools such as blood pressure or serum markers for HELLP syndrome such as alanine aspartate transferase. In twins, similar results were shown [82]. …”
Section: Clinical Role In the Diagnosis And Management Of Preeclampsiasupporting
confidence: 84%
“…It is known, however, that multifetal gestations exhibit different patterns of angiogenic factor serum levels with healthy twin pregnancies exhibiting a 3-fold increase in the sFlt-1/PlGF ratio as compared with singleton pregnancies. 16 Therefore, caution must be taken when applying the reference ranges and cutoffs found in this study to multifetal gestations. Furthermore, it is noteworthy that only a small proportion of patients in this European study are of other than white origin.…”
Section: Limitationsmentioning
confidence: 94%